Semantics Based on the Physical Characteristics of Facial Expressions Used to Produce Japanese Vowels - Shushi Namba (Behavioral Sciences, 2020)
Previous studies have reported that verbal sounds are associated—non-arbitrarily—with specific meanings (e.g., sound symbolism and onomatopoeia), including visual forms of information such as facial expressions; however, it remains unclear how mouth shapes used to utter each vowel create our semantic impressions. We asked 81 Japanese participants to evaluate mouth shapes associated with five Japanese vowels by using 10 five-item semantic differential scales. The results reveal that the physical characteristics of the facial expressions (mouth shapes) induced specific evaluations. For example, the mouth shape made to voice the vowel “a” was the one with the biggest, widest, and highest facial components compared to other mouth shapes, and people perceived words containing that vowel sound as bigger. The mouth shapes used to pronounce the vowel “i” were perceived as more likable than the other four vowels. These findings indicate that the mouth shapes producing vowels imply specific meanings. Our study provides clues about the meaning of verbal sounds and what the facial expressions in communication represent to the perceiver.